An assessment of residential satisfaction in public housing using Housing Habitability System Framework in Gombe, Northeast Nigeria - Maina, Joy Joshua (Penerbit Universiti Kebangsaan Malaysia, 2021)
Residential satisfaction has been employed to assess housing environments across several disciplines. However, measurement of variables remains an issue across large and small samples. This study assesses residential satisfaction in Gombe, Northeast Nigeria using the Housing Habitability System framework to ascertain it’s consistency across different locations and sample sizes. A mixed methodology including informal interviews and a questionnaire survey of 41 public housing residents in Gombe analysed in SPSS for descriptive and inferential statistics revealed that findings were consistent with four characteristics of residential satisfaction studies employing the framework identified across the country from previous studies. Specifically, results established that residents of public housing in Gombe were generally dissatisfied with their housing environments. Additionally, satisfaction followed the dwelling-neighbourhood-management sequence found in literature. Eight components extracted from principal component analysis reflect housing conditions in the study area. The study concludes that measurements based on tenets of Housing Habitability System framework produces consistent results across regions and different sample sizes and is beneficial for comparative purposes towards improvement of residential satisfaction research in Nigeria.